A coupled CFD-DEM simulation of fracture sealing: Effect of lost circulation material, drilling fluid and fracture conditions. (15th August 2022) - Lin, Chong; Taleghani, Arash Dahi; Kang, Yili; Xu, Chengyuan
Highlights: Flow curve-based integrated parameters well evaluate fracture sealing performance. LCMs mainly affect sealing performance by size, concentration, friction and elasticity. Fluid affects sealing performance of LCM by viscosity, injection rate and type. Fracture affects sealing performance of LCM by shape and surface roughness. Fluid-fracture forces, contact forces and friction forces dominate LCM sealing. Abstract: Lost circulation could be one of the most troublesome and expensive situations during drilling, especially in naturally fractured formations. Sealing fractures by granular lost circulation materials (LCMs) is one of the common methods for lost circulation control. However, this type of LCM has a limited effectiveness partly due to the poor understanding of how granular LCMs work. To fill this gap, a coupled CFD-DEM model is utilized for simulating the sealing process of a typical granular LCM (calcium carbonate) in a wedge-shaped fracture. In this paper, we first defined a set of comprehensive evaluation criteria for the sealing performance of LCMs, which include sealing probability, sealing time, location and stability of the seal, total loss volume and pressure gradient within the sealing zone. Effects of LCM, base fluid and fracture geometry on the sealing performance were investigated using the above-mentioned criteria based on differential pressure buildup, cumulative loss volume, and LCM loss rate, and differential pressure along depth. Our results show that LCM bridging and sealing in the fractures are initialed and controlled under interactive fluid-particle forces (drag force, viscous force and pressure gradient force), contact forces (normal and tangential) and friction forces (static and sliding). Essentially, it is the fluid-particle interactions, ratio of particle size to fracture width, volume concentration and friction effect that determine the fracture sealing performance. For the 1 mm–0.34 mm wedge-shaped fractures, sealing by LCM suspension with particle volume concentration of 9%, the critical bridging and sealing particle size are 200 μm and 330 μm, respectively. For the base simulation case considered in this paper, the critical bridging concentration and the sealing initiation concentration are both between 5% and 7%, and the critical sealing concentration is ranging between 7% and 9%. The critical coefficient of friction between particles for a stable fracture sealing varies between 0.2 and 0.4, and the critical coefficient of friction between particles and fracture surface for stable fracture sealing is ranging between 0 and 0.2. The critical Young's modulus of particles for dual-particle bridging is between 0.1 and 1 GPa. The critical fluid injection rate is ranging between 1.25 and 3 m/s beyond which the LCM cannot seal the fracture. The rest of factors affect LCM bridging and sealing by changing these four factors to some extents. Particle size, volume concentration, Young's modulus and the coefficient of friction of bridging granular LCM, and density, viscosity and injection rate of base fluid should be optimized synergistically to achieve an efficient fracture sealing. This research provides a better insight into the working principle of LCMs, which gives a solid scientific basis for LCM selection and design in practical problems.